EFFECTIVITY ANALYSIS OF NEUROPROTECTOR (VITAMIN B COMPLEX AND MECOBALAMIN) AS NEUROPATHIC PAIN SUPPORTIVE THERAPY IN ELDERLY WITH TYPE 2 DIABETES MELLITUS - ADI JAYA, MADE KRISNA; DWICANDRA, NI MADE OKA (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Neuroprotector (Vitamin B complex or mecobalamin)is often used as a supportive neuropathic pain therapy. The effectiveness of this drug remains controversial, especially in geriatrics with Type 2 diabetic neuropathy pains. The aim of this study was to compare the diabetes neuropathic pain reduction in elderly with and without neuroprotective supplementation. Method: The study was conducted by prospective cohort design. 132 agings were observed during 4 weeks at Neurology Polyclinic, Sanglah Public Hospital, Denpasar, Bali-Indonesia. Individuals undergoing the first-line neuropathic pain therapy who received neuroprotector supplementation were included in the exposure group (66 individuals), while those not receiving neuroprotective supplementations were included in the nonexposure group (66 individuals). The pain scores were measured by numeric rating scales instruments. The measured outcome was a decrease in diabetic neuropathic pain scores. Result: Both groups showed reduce on pain scores statistically different compared to baseline pain score (p<0.05). The comparison head-to-head on neuroprotector supplementation group showed significantly greater to reduce the pain score compared to nonexposure group (p<0.05). The relative risk of pain score reduction more than 2 units was 1.37 (confidence interval [CI]95%: 1.05-1.80)and the number need to treat was 5 (CI 95%: 3-28) compared to nonexposure group. Conclusion: Individuals who are undergoing the first-line neuropathic pain therapy and getting Vitamin B complex or mecobalamin supplementation had decreased pain intensity better than without supplementation therapy.